Distinct Clinicopathological Features and Prognosis of Emerging Young-Female Breast Cancer in an East Asian Country: A Nationwide Cancer Registry-Based Study. (7th May 2014) - Lin, Ching-Hung; Chuang, Po-Ya; Chiang, Chun-Ju; Lu, Yen-Shen; Cheng, Ann-Lii; Kuo, Wen-Hung; Huang, Chiun-Sheng; Lai, Mei-Shu; You, San-Lin; Tang, Chao-Hsiun
Abstract: Background: A rapid surge of young-female breast cancer (YFBC) has been observed in Taiwan and other East Asian countries. We recently reported that these cases of YFBC, in contrast to their Western counterparts, are predominantly luminal A subtype. YFBC in Asia may have distinct clinicopathological features and outcomes. Methods: Data collected prospectively by participating hospitals were retrieved from the Taiwan Cancer Database. A total of 15, 881 women with newly diagnosed stage I–III breast cancer in 2002–2006 were included. The age at diagnosis was categorized into nine 5-year groups (from <30 years to ≥65 years). Clinicopathological variables and patient disease-free survival (DFS) were compared by age group. Results: The rates of stage I, estrogen receptor-positive (ER+), and progesterone receptor-positive breast cancer were higher in the younger patients (<50 years) than in the older patients (≥50 years). Univariate analysis showed that the 40–44 and 45–49 age groups were significantly associated with longer DFS than the other age groups. In the ER+ subgroup, multivariate analysis consistently showed that the 40–44 age group was significantly associated with longer DFS than the other age groups except for the 45–49 age group. In contrast, multivariate analysis of the ER-negative subgroup revealed no significant difference of DFS between the 40–44 age group and other age groups. Conclusion: Emerging YFBC in Taiwan is uniquely associated with favorable pathological features and better outcomes and should not be regarded as the mirror image of its Western counterpart. Abstract : A rapid surge of young-female breast cancer (YFBC) has been observed in Taiwan and other East Asian countries. This study showed that emerging YFBC in Taiwan is uniquely associated with favorable pathological features and better outcomes and should not be regarded as the mirror image of its Western counterpart.